Performing propaganda : musical life and culture in Paris, 1914-1918 - Moore, Rachel, 1981 December 14- (Boydell & Brewer Ltd., 2017)
This book looks at musical life in Paris between 1914 and 1918. It examines how Western art music became a central part of the home-front war effort, employed by both musicians and government as a powerful tool of propaganda. Drawing on a diverse range of archival material, the book explores how various facets of French musical life served, in very different ways, as propaganda. In short, it explores why music mattered during a period of prolonged conflict, whether as emotional catalyst, weapon, or tool.
Keywords: World War, 1914-1918 -- Music and the war.; World War, 1914-1918 -- Propaganda.; Music -- France -- Paris -- History and criticism -- 20th century.; Paris (France) -- Social life and customs -- 20th century.; Guerre mondiale, 1914-1918 -- Propagande.; Musique -- France -- Paris -- Histoire et critique -- 20e siècle.; HISTORY -- Europe -- Western.; Manners and customs; Music; Music and war; Propaganda; France -- Paris; 1900-1999; Criticism, interpretation, etc.